The Extended Bessel-Maitland Function and Integral Operators Associated with Fractional Calculus - Kelelaw Tilahun; Hagos Tadessee; D. L. Suthar (Journal of Mathematics)
The aim of this paper is to introduce a presumably and remarkably altered integral operator involving the extended generalized Bessel-Maitland function. Particular properties are considered for the extended generalized Bessel-Maitland function connected with fractional integral and differential operators. The integral operator connected with operators of the fractional calculus is also observed. We point out important links to known findings from some individual cases with our key outcomes.